SELECTION OF ANTIBACTERIAL PREPARATIONS IN PREGNANCY - S.A. Sher; A.V. Ostrovskaya (Педиатрическая фармакология)
The article focuses on issues related to the selection of drugs in infection processes during pregnancy. To eliminate fetal risk or mitigate it a rational selection of drugs and their optimal dosage are required. It provides key groups of antimicrobial drugs ranked by their safety for the fetus under US FDA classification. To select treatment courses using antibacterial drugs that are safe to pregnant women, the attending physician should have reliable and up-to-date information on fetal risk posed by their application. Despite the existence of many various antibiotics, growth of sustainable bacterial flora requires the development and introduction of new antimicrobial drugs.Key words: drugs, antimicrobial substances, antibiotics, pregnancy, embryo, fetus, fetal risk.